Exploring dental students' knowledge on oral cancer prevention: a cross-sectional study in Moldova, Armenia, and Belarus - Olga Golburean; Diana Uncuta; Gayane Manrikyan; Natalia Shakavets; Izabella Vardanyan; Marina Markaryan; Ferda Özkaya; Daniela-Elena Costea; Tarig Al-Hadi Osman (BMC Oral Health)
Abstract Background Survival rate of patients with oral cancer (OC) remains to be very low despite advancements in therapy and surgical techniques. This is attributed to the fact that most OC cases are discovered at a late stage. Dentists play a vital role in early detection of OC through oral mucosal examination, and in informing the patients about avoidable risk factors of the disease, such as tobacco and excessive alcohol use. This study aimed at evaluating knowledge about OC among dental students in Moldova, Armenia and Belarus; three former soviet countries with high rates of tobacco use. Methods This was a cross-sectional, multi-country study based on self-administered questionnaire. Dental students in their clinical years at three dental faculties in Moldova, Armenia and Belarus were invited to participate in the study. Data collection took place during the period May to September 2019. Association between different categorical variables was investigated using Chi-squared test. A knowledge score ranging from 0–14 was constructed from the obtained data. Differences in the knowledge score between different groups of students was investigated using either student`s t-test whenever comparing two groups, or One-way ANOVA with Bonferroni`s correction for three or more groups. The level of significance was set to 0.05 for all statistical tests. Results A total of 642 dental students participated in the study. The mean knowledge score was found to be 6.62 ± 2.61, with 45% of the students scoring below the mean. Students from Belarus had the highest score (7.3 ± 2.14) in comparison to Armenia (6.66 ± 2.64) and Moldova (5.66 ± 2.81), as revealed by ANOVA test. However, we observed a significant increase (p-value < 0.001, ANOVA) in the students` knowledge score as they proceed through study years from third (6.07 ± 2.61) to fifth year (7.49 ± 2.48). In addition, we found that Students with current or previous cigarette smoking habits had significantly (p-value < 0.001, student`s t-test) lower mean knowledge score (5.96 ± 2.82) when compared to students who have never been smokers (6.98 ± 2.42). Conclusions The present study reveals notable gaps in OC knowledge and concerning tobacco use behaviors among dental students in Moldova, Belarus, and Armenia. By providing comprehensive education on risk factors and addressing personal habits, dental schools can better prepare future professionals to play a critical role in OC prevention and management.